Dissociable effects of cannabis with and without cannabidiol on the human brain's resting-state functional connectivity. (July 2019) - Wall, Matthew B; Pope, Rebecca; Freeman, Tom P; Kowalczyk, Oliwia S; Demetriou, Lysia; Mokrysz, Claire; Hindocha, Chandni; Lawn, Will; Bloomfield, Michael AP; Freeman, Abigail M; Feilding, Amanda; Nutt, David; et al.
Background: Two major constituents of cannabis are Δ 9 -tetrahydrocannabinol (THC) and cannabidiol (CBD). THC is the main psychoactive component; CBD may buffer the user against the harmful effects of THC. Aims: We examined the effects of two strains of cannabis and placebo on the human brain's resting-state networks using fMRI. Methods: Seventeen healthy volunteers (experienced with cannabis, but not regular users) underwent three drug treatments and scanning sessions. Treatments were cannabis containing THC (Cann−CBD; 8 mg THC), cannabis containing THC with CBD (Cann+CBD; 8 mg THC + 10 mg CBD), and matched placebo cannabis. Seed-based resting-state functional connectivity analyses were performed on three brain networks: the default mode (DMN; defined by positive connectivity with the posterior cingulate cortex: PCC+), executive control (ECN; defined by negative connectivity with the posterior cingulate cortex: PCC−) and salience (SAL; defined by positive connectivity with the anterior insula: AI+) network. Results: Reductions in functional connectivity (relative to placebo) were seen in the DMN (PCC+) and SAL (AI+) networks for both strains of cannabis, with spatially dissociable effects. Across the entire salience network (AI+), Cann−CBD reduced connectivity relative to Cann+CBD. The PCC in the DMN was specifically disrupted by Cann−CBD, and this effect correlated with subjective drug effects, including feeling 'stoned' and 'high'. Conclusions: THC disrupts the DMN, and the PCC is a key brain region involved in the subjective experience of THC intoxication. CBD restores disruption of the salience network by THC, which may explain its potential to treat disorders of salience such as psychosis and addiction.